Exploring Mesoamerica / John M.D. Pohl. - Pohl, John M. D. (Places in time., 1999)
"In Exploring Mesoamerica, the second volume in the Places in Time series, John M.D. Pohl takes us on a guided tour of eighteen well-known archaeological sites of Mesoamerica, bringing to life the civilizations that once flourished there." "Illustrated with photographs, maps, reconstructions, and site plans, Exploring Mesoamerica examines sites from 1500 B.C. to 1519 B.C., from Izapa, Tikal, and Palenque to Cacaxtla, Paquime-Casas Grandes, and Tenochititlan. Each site is a time capsule reflecting the cultural lifespan of that particular region and providing clues to the societal evolution of ancient Mesoamerica as a whole. Every chapter describes the history of a site's excavation and its most revealing architectural treasure, then goes on to discuss the people who lived there and the technological advances, class structures, and spiritual beliefs that characterized their culture. From intricate terraced gardens to palatial residences, from complex celestial calendars to thriving trade networks, Mesoamerican civilization springs into bold relief in this carefully researched volume. Every site discussed is fully accessible to the public and the author provides their locations, listing the museums that contain the primary artifacts for each."--Jacket.